Cross-border acquisition or greenfield investment? The role of investor sentiment - Li Dong; Jinlong Chen (Frontiers in Psychology, 2023)
When a firm invests in a foreign market, it has to choose between cross-border acquisition and greenfield investment. The impact of investor sentiment on the establishment mode of firm outward foreign direct investment (OFDI) has not been investigated by previous literature. Based on the data of Chinese listed companies between 2007 and 2019, this paper finds that firms prefer cross-border acquisition over greenfield investment when investor sentiment is high, and equity issuance and catering to sentiment are transmission channels. Cross-sectional test results show that the impact of investor sentiment on the establishment mode is concentrated in non-state-owned enterprises, and is stronger in non-eastern province firms and in technology-intensive OFDI. After various robustness tests, the main conclusion remains unchanged. This paper not only finds a new determinant that affects the establishment mode of OFDI but also enriches the research on the economic consequences of investor sentiment, which helps understand the role of investor sentiment in firms’ internationalization decisions.